814 VHA's TeleSleep Program improves rural Veteran access to sleep care through expansion of telehealth networks. (3rd May 2021) - Sarmiento, Kathleen; Kuna, Samuel; Boudreau, Eilis; Atwood, Charles; Pineda, Lilibeth; Thompson, William; Zeidler, Michelle; Fields, Barry; Uzzaman, Afifa; Totten, Annette; Smith, Connor; Folmer, Robert; et al.
Abstract: Introduction: Rurality is a known contributor to health disparities, including Sleep medicine. Over 1 million (>350, 000 rural, >650, 000 non-rural) Veterans who received care from VHA in 2020 have obstructive sleep apnea (OSA). VHA's Office of Rural Health (ORH) TeleSleep Program (FY17-20) aimed to increase access to sleep care for rural veterans by establishing telehealth services at 12 hubs and 63 spokes across the country. The TeleSleep program has three components: (1) Telemedicine; (2) Home Sleep Apnea Testing (HSAT); and (3) REVAMP (Remote Veterans Apnea Management Platform), a web-application for comprehensive sleep apnea care. Methods: Each of the three TeleSleep components was evaluated independently using specific metrics. We report here on the impact of leveraging telemedicine to improve access to sleep care. Patient care encounters are defined by VA-specific stop codes and are thus identifiable as telehealth or in-person visits. Data used in the evaluation were obtained from the VA Corporate Data Warehouse. Results: During FY20, 33, 743 rural Veterans had 74, 458 sleep encounters within the TeleSleep network. Visits included in-person care, virtual initial and follow up visits, electronic consultations, asynchronous telehealth (remote monitoring of PAP data and HSAT), remote PAP initiation by video or phone, and email exchanges between patients and providers. Between FY17-20, the number of rural Veterans seen for sleep-related disorders at TeleSleep sites tripled (from 10, 702 to 33, 743), and the number of encounters for sleep-related disorders more than doubled (from 32, 894 to 74, 458). In FY20, 72% (up from 53% in FY18) of rural Veterans at the TeleSleep hubs or spokes had at least one virtual sleep visit. This was significantly higher than non-TeleSleep VA sites where only 64% of rural Veterans had virtual visits (72% vs. 64%; p<0.001). In addition, the proportion of Veterans who had face-to-face only visits (28% at TeleSleep sites vs. 36% at non-TeleSleep sites; p<0.001) indicates that the TeleSleep program was highly successful in promoting virtual (instead of face-to-face) visits. Conclusion: The ORH TeleSleep Program has improved access to comprehensive sleep care for rural Veterans by increasing the proportion and type of sleep visits conducted virtually vs. in person. Support (if any): Funding provided by VHA Office of Rural Health